IMPACT OF TEAMS SOCIO- DEMOGRAPHIC FACTORS ON ORGANISATIONAL LEADERSHIP BEHAVIOUR IN ICT INDUSTRY - Kumar, Puneet; Pasumarthi, Srinivas Subbarao (International Journal of Psychosocial Rehabilitation, 2020)
Organizational leadership behaviour (OLB) plays significant role in the formation of organizations (Larsson & Vinberg, 2010). A leader’s behaviour can influence satisfaction of the employees; which will be mirrored in their performance and productivity of the organization. The Leadership style can have major influence on individual’s outcomes, so it becomes imperative for leaders to be more aware about their behaviours and adapt it to inspire their team members, and furthermore to give them a chance to express their creativity in a manner that can have gainful effect on the organization as well as employees. The leaders can create high spirit work environment, which has enduring impact on the inspiration of employees to invest in themselves, with the aim of contributing in organization’s triumph (Mubarak, 2014). The objective of this paper is to study the Socio Demographic Factors of the team Influencing OLB in ICT Industry for which data of 110 respondents have been collected from people working in ICT industry. For data analysis, one-way ANOVA has been used to check the influence of Socio Demographic Factors on OLB. As per the findings of this study, gender of team member is the factor which has shown significant influence on OLB.